Pengendalian Hama Kelapa Larva Kumbang Badak (Oryctes rhinoceros, L.) Instar III Dengan Metarhizium anisopliae, Metch. yang Ditumbuhkan Pada Berbagai Macam Dedak Gandum - Astuti, Agung; Sudarsono, Darmawan Suryo; Prabowo, Agus (Universitas Muhammadiyah Yogyakarta, 2005)
The research objectives were to observe the growth and spore production of Metarhizium anisopliae grown at wheat-pollard and wheat-brand and to test the M. anisopliae pathogenicity on instar III rhinoceros beetle larva of coconut pest (Oryctes rhinoceros, L.). The research were executed in 3 phases : (1) Regeneration phase of M. anisopliae, the experiment was arranged in single factor CRD with 3 kinds of wheat and 3 replications. The influences of the treatments on biomass, spore number and spore viability were observed then; (2) lethal dosage (LD50) determination phase; and (3) phatogenicity test of M. anisopliae, the experiment was arranged in 3 x 3 factorial CRD, where the first factor was the kinds of wheat (i.e. Pollard, Brand and Pollard Brand) and the second factor was the dosage of biopesticide (i.e. 0,5 LD50 LD50 and 2 LD50). The phatogenicity testing was conducted to evaluate the effects on toxicity, mortality speed, and effication percentage. The result indicated that the wheat-brand was the better medium for M. Anisopliae than the pollard and the pollard-brand ones. The average spore number (1021,67 x 1014 spora/ml), biomass (95,94 g) and the viability (127,00 x 108 spora/ml) were significantly higher than the others. The lethal dosage obtained was 6,70g to gave the mortality percentage (73,33 %) and the effication percentage (73,33 %) significantly higher than the other treatments.